مکی عہد نبویﷺ کے وفود کی دعوتی خدمات : تجزیاتی مطالعہ: Invitational Services for the Delegations of the Prophet in Meccan Period: An Analytical Study (Al-Qamar, 2021)
The chain of Da'wah to Allah continues from Adam (A.H). The preaching of the Oneness of Allah has been the first duty of the Holy Prophets. The Holy Prophet ﷺalso adopted the same duty and continued to preach Islam day and night. For this, He prepared his followers in a good way and also told them the method of preaching Islam to others. He who is guided by the Prophet of Allah does not need to be guided by anyone else. The Companions used to learn the style of preaching and convey this message to others in the best way. If we take a closer look at the time of the Prophetﷺ , it was a difficult stage in which all kinds of enemies were present. Those who took the name of Islam could not be tolerated under any circumstances. In the time of the Prophet ْﷺthe work of da'wah required great wisdom. The infidels of Makkah wanted to convert Muslims from Islam in every possible way. And they wanted to keep the same outdated system by practicing their religion. But the Companions of the Holy Prophet ﷺ who received the title of the Al.Sabiqoon Awaloon faced all sorts of problems and lit the candle of Islam which soon spread the light of Islam all over the world. The individual and collective efforts of the Companions in spreading Islam in the beginning of Islam cannot be forgotten. The Companions did not spare any effort to spread the religion of the Prophet ﷺ at the expense of their family, tribe and the infidels of Makkah.The Companions continued to perform this duty with full perseverance as per the instructions of the Holy Prophetﷺ .But the Prophet ﷺtaught his followers the method of Da'wah in such a way that they followed it and spread Islam to the world. This article gives an overview of the delegations that came from different parts of the world during the Makki erra. What was the attitude of the Prophet ﷺ towards these delegations and what teachings should he give to those whom he sent to other areas?۔ Even in this age, relations with other countries can be established only in accordance with the teachings of the Holy Prophetﷺ. Foreign relations and policy must also be formulated in accordance with Islamic principles in order to spread Islamic teachings effectively.
Keywords: Islamic civilization; Dawha; Deligations; Companions; Relations